Abnormal Tryptophan Metabolism in HIV and Mycobacterium tuberculosis Infection - Wang, Xiaolei; Mehra, Smriti; Kaushal, Deepak; Veazey, Ronald S.; Xu, Huanbin (Frontiers in Microbiology, 2021)
Host metabolism has recently gained more attention for its roles in physiological functions and pathologic conditions. Of these, metabolic tryptophan disorders generate a pattern of abnormal metabolites that are implicated in various diseases. Here we briefly highlight the recent advances regarding abnormal tryptophan metabolism in HIV and mycobacterium tuberculosis infection and discuss its potential impact on immune regulation, disease progression, and neurological disorders. Finally, we also discuss the potential for metabolic tryptophan interventions towards these infectious diseases.